Terminological Resources from the Swedish Migration Agency - Dahlberg, Simon; Institute for Language and Folklore (Institute for Language and Folklore, 2020)
Files with term lists, delivered by e-mail directly from the Swedish Migration Agency.

One Swedish-English term list that constitutes the greater part of this material, plus two smaller monolingually Swedish term lists with explanations to each term. The former was delivered directly to us by the agency (via e-mail) and the two latter were downloaded from their website.

Filer med termlistor levererade per e-post direkt från Migrationsverket.

En svensk-engelsk termlista som utgör större delen av materialet, samt två mindre enspråkigt svenska termlistor med förklaringar till varje term. Den tidigare levererades till oss direkt av Migrationsverket (per e-post), och de två senare nedladdades från deras webbplats.
Terminologiska resurser från Migrationsverket
Keywords: immigration policy; invandringspolitik; Emigration and Immigration; Utvandring och invandring; Legislation and legal systems; Lagstiftning och rättssystem; International politics and organisations; Internationell politik och organisationer; Conflict, security and peace; Konflikter, säkerhet och fred; SOCIAL WELFARE POLICY AND SYSTEMS; SOCIAL VÄLFÄRDSPOLITIK OCH VÄLFÄRDSSYSTEM; SOCIETY AND CULTURE; SAMHÄLLE OCH KULTUR; Social Sciences; Samhällsvetenskap; Languages and Literature; Språk och litteratur